Effect of exogenous Brassinolide on improving fruit quality and reducing fruit cracking in Junzao jujube - YANG Cheng; WANG Zhenlei; ZHANG Chuanjiang; LIU Wei; WU Cuiyun; LIN Minjuan (Guoshu xuebao)
[Objective] Xinjiang is the largest jujube producing area in China, and Junzao is one of the main cultivated varieties in Xinjiang. Jujube fruit cracking problem has been plaguing the development of jujube industry, causing serious economic losses. Brassinolide can improve fruit quality, increase fruit hardness, regulate fruit endogenous hormone content and increase peel toughness. Therefore, the purpose of this study was to investigate the effects of different concentrations of brassinolide on fruit cracking, nutritional quality, texture, cell wall metabolic enzyme activity and endogenous hormone content in Junzao. [Methods] In this experiment, 10-year-old trees were used as experimental materials. Different concentrations of brassinolide (1 mg·L-1, 2 mg·L-1 and 3 mg·L-1) were sprayed during fruit expansion, and clear water was sprayed as the control. The fruit cracking rate, fruit quality (soluble solids, soluble sugar, titratable acid, hardness, adhesiveness, elasticity, chewiness and adhesiveness), peel cell wall metabolic enzymes (catalase (CAT), peroxidase (POD), superoxide dismutase (SOD), cellulase, pectinase) and peel endogenous hormones (GA3, IAA and ABA) were measured at green-ripening stage, white-ripening stage, color-turning stage, half-red stage and full-red stage. Excel 2016 was used for data collection and analysis, SPSS 27.0 was used for significance analysis, Origin 2021 was used for mapping, and correlation analysis and principal component analysis were carried out for each index at whiteripe stage. [Results] Spraying brassinolide during the fruit enlargement period of Junzao can significantly reduce the fruit cracking rate. The increase of fruit cracking rate with different treatments at white-ripe stage was the largest, which was the key period of fruit cracking. The fruit cracking rate was the highest at the whole-red stage, which was the peak period of fruit cracking. The fruit cracking rate of different brassinolide concentrations was 6.38%, 4.63% and 4.48% lower than that of the control. The soluble solids content in fruits treated with brassinolide increased by 2.49%, 5.09% and 33.84%, respectively, and the soluble sugar content increased by 3.35%, 12.72% and 7.08%, respectively, compared with the control. Spraying brassinolide can increase fruit hardness, chewiness and gumminess. The activities of CAT and SOD in each treatment decreased with the increase of maturity. The CAT activity in the peel under different brassinolide concentrations increased by 18.54%, 39.07% and 98.01%, respectively, compared with the control. The SOD activity increased by 55.32%, 67.25% and 71.18%, respectively, and the POD activity decreased by 24.66%, 1.15% and 32.06%, respectively, compared with the control. The activities of cellulase and pectinase reached the peak at the white-ripening stage, and then decreased with the increase of fruit maturity. The activities of pectinase at the whole-red stage with each treatment were 6.92%, 7.75% and 13.91% lower than those of the control, respectively. The content of endogenous hormones in peel changed significantly with fruit growth and development. GA3 and IAA showed a downward trend, and GA3 and IAA in the peel of fruits treated with brassinolide were significantly or extremely significantly higher than those in the control at each stage. Gibberellin GA3 increased by 8.30%, 24.70% and 14.07%, respectively, at the whole-red stage compared with the control. IAA content increased by 312.12%, 198.48% and 457.58%, respectively. The ABA content was significantly reduced by 16.30%, 22.47% and 17.10%, respectively, compared with the control. Hormone balance is one of the factors affecting fruit cracking. At the full-red stage of fruit, the ratio of (GA3 + IAA)/ABA in the pericarp of fruits treated with brassinolide and water (control) was 49∶57∶55∶33, respectively, which was higher than that of the control. The correlation between different concentrations of brassinolide treatment and control at white-ripe stage was analyzed. The analysis showed that the fruit cracking of jujube fruit was related to many factors such as cell wall metabolic enzymes, fruit quality and endogenous hormones. Fruit cracking rate was significantly and positively correlated with titratable acid content. There was a significant positive correlation with ABA content. It was significantly and negatively correlated with hardness, adhesion, CAT activity and GA3 content. There was a significant negative correlation with SOD activity. Principal component analysis showed that the main traits affecting fruit quality were hardness, chewiness, adhesiveness, SOD activity, GA3 content and fruit cracking rate. [Conclusion] Spraying brassinolide can effectively reduce the fruit cracking rate of Junzao, and improve fruit soluble solids content, soluble sugar content, fruit hardness, chewiness and adhesiveness. The CAT and SOD activities as well as GA3 and IAAcontents in the pee increased, and the cellulase and pectinase activity as well as ABA content decreased. The cracking resistance was improved and the cracking rate was reduced. Among them, spraying 1 mg·L-1 concentration of brassinolide had the best effect on preventing fruit cracking.